Preparation and characterization of chemically deposited nickel sulphide film and its application as a potential counter electrode. (25th July 2016) - Ray, Jaymin; Patel, Mitesh; Ghediya, Prashant; Chaudhuri, Tapas K
Abstract: Nickel sulphide (NiS) film has emerged as a counter electrode in many applications, such as thin film batteries, dye sensitized solar cells, and supercapacitors. In this regard, we report the direct liquid coating of pure hexagonal NiS films on glass using a precursor solution of nickel–thiourea complex. A uniform and void free film is observed using scanning electron microscopy. The room temperature electrical conductivity of ∼5 × 10 3 S cm −1 and the positive thermoelectric power (+6 μ V K −1 ) specify p-type conduction. The temperature variation conductivity in the range 77–300 K depicts the transition of NiS films from conducting to semi-conducting behaviour at certain transition temperatures. Preliminary results from a cyclic voltammetry study shows the feasibility of NiS films as counter electrodes.